MAKNA VERBA NERAU DAN MEZASU DALAM SINONIM BAHASA JEPANG - I Gusti Ayu Regina Dhira; Ni Wayan Meidariani; Wahyu (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2025)
Japanese is a foreign language with a wide variety of words. One such variation is in the verb class. This article discusses the meaning and use of the verbs "nerau" and "mezau" in Japanese ruigigo. This research focuses on sentences used by native Japanese speakers. Data collection was conducted through interviews and the recording technique. The author conducted direct interviews with Japanese speakers while recording sentences containing synonyms for the verbs "nerau" and "mezau" in Japanese. The data were analyzed using a contextual meaning approach (Pateda, 2010) with their presentation in Japanese sentences. The data found that in Japanese, the verb "nerau" has the following meanings: aiming for position/status, attacking with words, wanting a scholarship, wanting to win an election, seeking a large profit, pushing an enemy's head, shooting and seducing a bottle, fishing and seducing fish, and wanting a salary increase. Meanwhile, the verb 'mezasu' has the following meanings: focusing on customer satisfaction, aiming to pass an exam, aiming for a promotion, aiming for economic stability, aiming for a higher level, and aiming for the best service. The data shows that the verbs 'narau' and 'mezasu' have different meanings and usages depending on the context.